Grenada : Staff Report for the 2014 Article IV Consultation and Request for an Extended Credit Facility Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that Grenada's economy continues to face significant headwinds after a decade of natural disasters and economic shocks coalesced into a deep economic crisis by 2011-2012. Economic activity declined by more than 8 percent of GDP from peak to trough (2008-2012) as tourism and construction collapsed. After almost four years of decline, real GDP grew by 1.5 percent in 2013. To address the fiscal crisis, the authorities have initiated fiscal adjustment as part of their 2014 budget, and have subsequently approved a large package of revenue measures needed for the targeted consolidation.